PELAKSANAAN PASTORAL CARE PERAWAT DI RUANG ICU RS. SANTA ELISABETH MEDAN - Connie Sianipar (Jurnal Keperawatan Priority, 2021)
Pastoral care activities had to actualize the love of God in the life of the faith community. The problem, in this case, is the large number of pastoral care that has not implemented in the hospital, in this case, is being carried out as motivated, provide comfort, feel supportive, relax, calm and peaceful because it can reduce anxiety and anxiety in dealing with the internal pain healing process. This study aims to determine the implementation of pastoral care by nurses in the trigger room of Elisabeth Medan Hospital in 2019. The type of research used is descriptive research with a cross-sectional approach. The population in this study was 30 nurses in the ICU room at Elisabeth Medan Hospital. The sampling technique uses total sampling. The results of this study in the implementation of pastoral care by nurses in the trigger room were both 80% (24 nurses), enough 16% (5 nurses), and less carried out were 4% (1 nurse). The implementation of pastoral care by nurses in the trigger room of Elisabeth Medan Hospital was well implemented, with activities carried out by nurses such as religious assistance, spiritual assistance, pastoral counseling, sick people's visits, and mentoring. From the implementation of pastoral care, the role of health workers or nurses was important in implementing pastoral care for healing, sustaining, guiding, and reconciling.